Komunikacja interpersonalna kobiet z zaburzeniem osobowości typu borderline w związkach kohabitacyjnych - Bakiera, Lucyna; Czarnecka, Anna (Człowiek i Społeczeństwo, 2020)
The authors discuss in the article interpersonal communication in cohabitation relationships of women with a borderline personality disorder. 91 women aged between 21 and 40 who were in a consensual relationship participated in the research. The classification of the respondents to the criterion group was determined by the result obtained in the Borderline Personality Inventory (BPI) by F. Leichsenring in the Polish adaptation of Lidia Cierpiałkowska. 43 women were included in the criterion group, and the control group consisted of 48 women. The research also used the Marriage and Partnership Communication Questionnaire by Maria Kaźmierczak and Mieczysław Plopa. The analysis of the obtained results showed that women with borderline personality disorder show more depressing and less supportive and engaged communication behaviors compared to women without this disorder, both in self-perception and in the assessment of the partner’s communication behavior.